POLITIC SHOCK: Is lta Threat to Liberal World Order? - Desai, Meghnad; Aneet, (Gyan Management Journal, 2017)
The elevation of N arendra Modi and Donald Trump to top government positions in their respective countries, the significance of their rise and whether the old liberal world order has collapsed are among a bevy of issues Lord Meghnad Desai analyses in his new book. In "Politic Shock: Trump, Modi, Brexit & the Prospect for Liberal Democracy", Desai makes a study of how Modi and Trump won the elections.Desai, who sits as a Labour Peer in the UK's House of Lords, navigates the issues of populism and nationalism which he says now are cast as "undesirable" tendencies and adds it is "presumptuous" to cast either as an "unmitigated bad"."Modi won because he had a message which carried to the new voters who were children when the riots had taken place. They did not read newspapers but relied on social media. Modi had mastered the social media technology. He used Twitter imaginatively, made himself accessible online with a campaign team ever ready to respond to queries. This was the new technology of campaigning which the other parties were slow to replicate," Desai writes."Rahul Gandhi, the leader of the Congress party and the son, grandson and great-grandson of prime ministers, was younger than Modi but had no penchant for social media. Rather like (Hillary) Clinton, the Congress and Rahul Gandhi had a sense of entitlement. Power rightfully and due to historical primacy belonged to him. Modi was an interloper," says the book, published by Rupa.
Keywords: government; Politic Shock; Twitter; Liberal Democracy